Women Education in India: Need and Barriers: Breaking the Chains: Examining Women's Education and Overcoming Barriers in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Education is the process of becoming critically aware of one's reality in a manner that leads to effective action upon it. An educated man/woman understands his/her world well enough to deal with it is effectively. Education is important for everyone but it is especially significant for girls and women. Women's education is an instrument for liberation of Indian society. In the past, women did not receive any education at all. They were not allowed to come out of the four walls of their houses. Domestic works were their only education.